Free fatty acid receptors as therapeutic targets for the treatment of diabetes - Ichimura, Atsuhiko; Hasegawa, Sae; Kasubuchi, Mayu; Kimura, Ikuo (Frontiers in Pharmacology, 2014)
Nutrition regulates energy balance; however, dysfunction of energy balance can cause metabolic disorders, such as obesity and diabetes. Fatty acids are an essential energy source and signaling molecules that regulate various cellular processes and physiological functions. Recently, several orphan G protein-coupled receptors were indentified as free fatty acid receptors (FFARs). GPR40/FFAR1 and GPR120/FFAR4 are activated by medium- and/or long-chain fatty acids, whereas GPR41/FFAR3 and GPR43/FFAR2 are activated by short-chain fatty acids. FFARs are regarded as targets for novel drugs to treat metabolic disorders, such as obesity and type 2 diabetes, because recent studies have showed that these receptors are involved in the energy metabolism in various tissues, including adipose, intestinal, and immune tissue. In this review, we summarize physiological roles of the FFARs, provide a comprehensive overview of energy regulation by FFARs, and discuss new prospects for treatment of metabolic disorders.